Research and fabrication of toxic filter materials from Tra Bac coconut shell activated carbon applied in the manufacture of personal respiratory protection devices - Bui Van Tai; Mai Van Phuoc; Pham Thi Phuong; Nam, Dao (Journal of Military Science and Technology, 2022)
This paper presents the results of research on making materials to adsorb toxic acidic gases, organic substances from Tra Bac coconut shell activated carbon, and combined with chemical treatment on the laboratory scale. Methods were used for this study consisting of SEM, EDS; BET, and DPC5 (kinetic adsorbent). The results showed that the fabricated filter material has a surface area of 664 m2/g, calculated according to BET, has a protection time with benzene vapor (L= 5 cm, Co(vapor) = 18 mg/L) of 56 minutes; protection time with HCl acid vapor (L= 5 cm, Co (vapor) = 1.1 mg/L) is 280 minutes. The results of the study have exhibited a good ability to filter benzene vapor and HCl vapor. This material has the potential for use in the manufacture of personal respiratory protective equipment.